Low contralateral neck recurrence risk with ipsilateral neck radiotherapy in N2b tonsillar squamous cell carcinoma. (April 2023) - Natesan, Divya; Cramer, Christina K.; Oyekunle, Taofik; Niedzwiecki, Donna; Brizel, David M.; Mowery, Yvonne M.
Highlights: Many cT1-2N0-2b tonsil cancer patients are treated with ipsilateral neck radiation. Most with ipsilateral radiation had limited primary extension and pretreatment PET. No contralateral neck recurrences were observed in patients with N2b disease. Bilateral neck radiation may not be indicated in all patients with N2b disease. Abstract: Objectives: To characterize factors including nodal burden, pre-treatment imaging, and other patient factors which may influence the role of ipsilateral neck radiotherapy (IRT) in tonsillar squamous cell carcinoma (SCC) with multiple involved ipsilateral nodes. Methods: Patients with cT1-2N0-2bM0 (AJCC 7th edition) tonsillar SCC treated with definitive radiation therapy (RT) at Duke University Medical Center from 1/1/1990–10/1/2019 were identified. Patient, tumor, and treatment characteristics were compared between those that received bilateral neck RT (BRT) versus IRT. Recurrence-free survival (RFS) was estimated with Kaplan-Meier method. A subset analysis of patients with N2b disease was performed. Patterns of recurrence were analyzed. Results: 120 patients with cT1-2N0-2b tonsillar SCC were identified, including 71 with N2b disease (BRT: n = 30; IRT: n = 41). Median follow-up was 80 months (range: 7–209). No N2b patients who received IRT had > 1 cm of soft palate/base of tongue extension. N2b patients treated with IRT had a median of 3 (range 2–9) involved lymph nodes, with median largest nodal dimension of 2.8 cm (range 1.3–4.8 cm). 93 % of N2b patients who received IRT had staging by PET/CT, and 100 % received IMRT. For N2b patients treated with IRT, there were no contralateral neck recurrences, and 10 year RFS was 95 % (95 % CI 82 %–98 %). Conclusions: For patients treated with IRT for well-lateralized N2b tonsillar SCC, we observed high rates of local control with no observed contralateral neck recurrence. These data suggest that BRT is not universally necessary for patients with multiple involved ipsilateral nodes, particularly in the setting of baseline staging with PET/CT.